ZnO-Activated Carbon Blended as a Catalyst for Oxidative Desulfurization of Dibenzothiophene - Wega Trisunaryanti; Satriyo Dibyo Sumbogo; Safa Annissa Novianti; Dyah Ayu Fatmawati; Maria Ulfa; Yatim Lailun Nikmah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
The problem of sulfur content in heavy oil is a challenge for researchers to meet the needs of environmentally friendly fuels. The catalyst preparation plays an important role in the desulfurization process. The synthesis of ZnO-activated carbon as a catalyst and its activity in oxidative desulfurization (ODS) reaction has been successfully carried out. In this work, the ZnO and activated carbon (AC) were blended by a solid-solid reaction. The ZnO, AC, and ZnO-AC were then characterized using acidity test with pyridine vapor adsorption, Fourier Transform Infra-Red (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX), and Surface Area Analyzer (SAA). ODS of dibenzothiophene (DBT) reaction was performed by using H2O2 under variation of the reaction time (30, 60, 120, and 150 min) for the ZnO-AC catalyst. The efficiency of ODS-DBT was analyzed by a UV-Visible spectrophotometer. The XRD analysis result showed that ZnO-AC blended displays new crystal peaks of Zn in the AC diffractogram. The surface area (734.351 m2/g) and acidity (4.8780 mmol/g) of ZnO-AC were higher than ZnO and AC themselves. ZnO-AC produced the highest efficiency of ODS-DBT which was 93.83% in the reaction time of 120 min. Therefore, the simple procedure of this physical blending was proved effective to homogenize between ZnO and AC into ZnO-AC so that it has good physicochemical properties as an ODS-DBT catalyst. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).